2018
DOI: 10.18565/aig.2018.8.77-84
|View full text |Cite
|
Sign up to set email alerts
|

Clinical value of changes of the transmigration activity of leukocytes in the diagnosis of severe preeclampsia

Abstract: Aim. To identify additional criteria for the diagnosis of severe preeclampsia (PE) in pregnant women based on an investigation of the expression of the early adhesion molecules, chemokine receptors, and markers of endothelial dysfunction in venous blood neutrophils and monocytes. Material and methods. One hundred and fifty patients with PE (74 with moderate PE, 76 with severe PE) and 70 women with a physiological course of pregnancy were tested for venous blood neutrophils and monocytes expressing adhesion mol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
(15 reference statements)
0
1
0
Order By: Relevance
“…According to Kudryashova et al (2019) , there is a correlation between low levels of CD62L+, CD99 + , CXCR1+ neutrophils, serum CXCL8, and adversely affected blood vessel elastic properties. In addition, another study found that CX3CR1+ monocyte and neutrophil levels were higher in PE patients ( Panova et al, 2018 ). These findings clarified that, possibly, in PE, activated endothelial cells themselves regulate how tightly neutrophils adhere to the endothelium.…”
Section: Role Of Cx3cl1 Chemokine In the Pathogenesis Of Pementioning
confidence: 99%
“…According to Kudryashova et al (2019) , there is a correlation between low levels of CD62L+, CD99 + , CXCR1+ neutrophils, serum CXCL8, and adversely affected blood vessel elastic properties. In addition, another study found that CX3CR1+ monocyte and neutrophil levels were higher in PE patients ( Panova et al, 2018 ). These findings clarified that, possibly, in PE, activated endothelial cells themselves regulate how tightly neutrophils adhere to the endothelium.…”
Section: Role Of Cx3cl1 Chemokine In the Pathogenesis Of Pementioning
confidence: 99%